Large-Scale Analysis of Kinase Signaling in Yeast Pseudohyphal Development Identifies Regulation of Ribonucleoprotein Granules. - Christian A Shively; Hye Kyong Kweon; Kaitlyn L Norman; Dattatreya Mellacheruvu; Tao Xu; Daniel T Sheidy; Craig J Dobry; Ivan Sabath; Eric E P Cosky; Elizabeth J Tran; Alexey Nesvizhskii; Philip C Andrews; et al. (PLoS Genetics)
Yeast pseudohyphal filamentation is a stress-responsive growth transition relevant to processes required for virulence in pathogenic fungi. Pseudohyphal growth is controlled through a regulatory network encompassing conserved MAPK (Ste20p, Ste11p, Ste7p, Kss1p, and Fus3p), protein kinase A (Tpk2p), Elm1p, and Snf1p kinase pathways; however, the scope of these pathways is not fully understood. Here, we implemented quantitative phosphoproteomics to identify each of these signaling networks, generating a kinase-dead mutant in filamentous S. cerevisiae and surveying for differential phosphorylation. By this approach, we identified 439 phosphoproteins dependent upon pseudohyphal growth kinases. We report novel phosphorylation sites in 543 peptides, including phosphorylated residues in Ras2p and Flo8p required for wild-type filamentous growth. Phosphoproteins in these kinase signaling networks were enriched for ribonucleoprotein (RNP) granule components, and we observe co-localization of Kss1p, Fus3p, Ste20p, and Tpk2p with the RNP component Igo1p. These kinases localize in puncta with GFP-visualized mRNA, and KSS1 is required for wild-type levels of mRNA localization in RNPs. Kss1p pathway activity is reduced in lsm1Δ/Δ and pat1Δ/Δ strains, and these genes encoding P-body proteins are epistatic to STE7. The P-body protein Dhh1p is also required for hyphal development in Candida albicans. Collectively, this study presents a wealth of data identifying the yeast phosphoproteome in pseudohyphal growth and regulatory interrelationships between pseudohyphal growth kinases and RNPs.